(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2018)
FlexRay is set to become a new standard for automotive communication replacing conventional protocols like CAN in applications like safety critical considering speed of operation, reliability and redundancy factors. A traditional approach is currently used to design a FlexRay node where a microcontroller with integrated FlexRay communication controller is being used as first choice by designers. But on the other side Field programmable gate arrays (FPGAs) are also gaining importance to be used in automotive systems where FPGA is the controlling device. In this paper a design approach for FlexRay communication node is proposed where different aspects that should be considered when a FlexRay communication node is designed are mentioned. Initial sections define major components that are required for communication node are described with function of each component explained. Later sections define a brief approach to design FlexRay communication node.